EFEKTIVITAS MEDIA KOMUNIKASI PEMASARAN MELALUI INSTAGRAM PADA @angkringan_mastumin - Maatoke serly verlinda; Hairunnisa (Jurnal Sosial-Politika, 2023)
In the current era, it is undeniable that with the rapid advancement of technology and information, people are very creative in utilizing the sophistication of technology and knowledge to fulfil people's social life. Instagram is the most used application today because Instagram is an application that focuses on the use of images and videos. This has happened in developing culinary promotions through Instagram in Samarinda to generate a sense of enthusiasm in the community, thus inviting the public to come. One of them is the culinary Angkringan Mastumin Samarinda, which uses Instagram social media as the basis for promoting its products, which has the account name @angkringan_mastumin, which has managed to get as many as 21.4 thousand followers. The method used is qualitative, with a research focus on the marketing mix. Based on the results of the research contained in the discussion chapter, the researcher concludes the formulation of the research problem that the marketing mix carried out by Angkringan Mastumin is very effective and running well, including the marketing mix according to Hartajaya product, price, promotion and distribution channel.